Human monoclonal antibodies against West Nile virus from Japanese encephalitis-vaccinated volunteers - Tatsuhiko Ozawa (2019)
© 2018 Elsevier B.V. West Nile virus (WNV) is a positive-sense single-stranded RNA flavivirus belonging to the Japanese encephalitis virus (JEV) serocomplex of the Flaviviridae family and causes mosquito-borne infections. Although most human infection cases are asymptomatic, approximately one in 150 infected individuals develops meningoencephalitis, with a mortality rate of 4–14%. While the development of human neutralizing antibody therapeutics against WNV is strongly anticipated, WNV is difficult to study in conventional laboratories due to its high safety level requirement. In this study, we established fully human WNV-neutralizing monoclonal antibodies from the peripheral blood mononuclear cells of inactivated-JEV-vaccinated individuals, and these antibodies exhibited WNV neutralization both in vitro and in vivo. Our results demonstrate a new antibody cross-reactivity strategy to develop immunological therapeutic reagents for WNV and other JEV serotype viruses.